(untitled) (Research, Society and Development, 2021)
This paper studies the association between dengue cases and climatic variables in the city of São Paulo, Brazil, in the period from 2001 to 2011. The main hypothesis is that climatic conditions, such as precipitation, humidity and temperature, are all correlated to the dengue spread in São Paulo. Randomization and Spearman rank correlation are applied over the collected dataset, and the estimated results show that only a higher temperature is correlated to an increase in the notification of new dengue cases in São Paulo, further reinforcing the fact that the Aedes aegypti mosquito is known to survive in distinct climatic conditions, greatly adapting itself to urban environments.